Reliable transmission of visible light communication data in lighting control networks. Issue 3 (1st May 2017) - Choi, Sang‐Il; Koh, Seok‐Joo; Lim, Sang‐Kyu; Kang, Tae‐Gyu
Abstract : Recently, the visible light communication (VLC) is considered as a future emerging technology in the telecommunication and lighting industry, as defined in the IEEE 802.15.7 standard. In the meantime, the ANSI E1.45 standard was made to provide VLC data transmissions from a VLC data server to a lighting device that is equipped with a VLC transmitter in lighting control networks. However, the ANSI E1.45 scheme cannot provide reliable transmissions of VLC data, and thus a lost data, if any, cannot be recovered. To overcome such limitation, timer‐based VLC data transmission schemes have been studied by applying the retransmission scheme of Internet. However, these schemes still have limitation that the lost VLC data cannot be recovered immediately. Hence, in this study, the authors propose new reliable transmission schemes for VLC data over lighting control networks. The proposed schemes are classified into the packet‐based (PRVS) and fragment‐based (FRVS) schemes. From performance analysis by simulation, the authors see that the FRVS gives the best transmission throughput among the four candidate schemes. In addition, it is shown that the proposed reliable transmission scheme can effectively perform the error recovery operation in the networks with packet losses, compared to the ANSI E1.45 scheme.